2012
DOI: 10.1063/1.3697983
|View full text |Cite
|
Sign up to set email alerts
|

Production of high-density high-temperature plasma by collapsing small solid-density plasma shell with two ultra-intense laser pulses

Abstract: Three-dimensional particle-in-cell simulations show that the anisotropic collapse of a plasma microshell by impact of two oppositely directed intense laser pulses can create at the center of the shell cavity a submicron-sized plasma of high density and temperature suitable for generating fusion neutrons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Prior publications have shown that it is possible to stabilize the radiation pressure drive of a compressed foil if the pulse can wrap around the plasma. 31,39 For this purpose, a hydrogen cone is used in case B instead of the gold cone. The cone has a wall density of 50n c , while the other parameters for the laser and the foil are the same as that in case A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior publications have shown that it is possible to stabilize the radiation pressure drive of a compressed foil if the pulse can wrap around the plasma. 31,39 For this purpose, a hydrogen cone is used in case B instead of the gold cone. The cone has a wall density of 50n c , while the other parameters for the laser and the foil are the same as that in case A.…”
Section: Resultsmentioning
confidence: 99%
“…The simulations are performed using the relativistic 2D3V PIC code LAPINE. 31,32 Our initial target set-up contains a cone and a foil at the tip, as depicted in Fig. 1.…”
Section: Simulation Modelmentioning
confidence: 99%
“…To analyze the process of the ionization-induced injection in multi-staged gas, 2D PIC simulations were performed in cartesian coordinates by using the LAPINE code. [33,34] A linearly polarized Gaussian laser propagates along z-axis from the left boundary of the simulation box with a wavelength of λ 0 = 0.8 µm, the spot radius of w 0 = 15 µm, the pulse duration of τ L = 33 fs. The normalized vector potential of the laser pulse is a 0 = eE L0 /m e ω 0 c = 1.8 where e is the electron charge, E L0 is the peak electric field, m e is the rest electron mass, ω 0 = 2πc/λ 0 is the laser frequency, and c is the speed of light, which corresponds to the pulse energy of 2.25 J.…”
Section: Simulation Modelmentioning
confidence: 99%
“…The target consists of a small hollow solid-density shell preceded by a guide channel filled with the NCD plasma. A short intense laser pulse can self-focus and channel [19][20][21][22] through the NCD plasma and enter the hollow shell by pushing aside the electrons in the former, creating around it an electron wake channel where the light pressure balances the space-charge field. Two-dimensional PIC simulation shows that as the laser pulse enters shell, the space charge field pulls back the expelled electrons in the wake channel, thereby closing it.…”
Section: Introductionmentioning
confidence: 99%